Upaya Meningkatkan Pemahaman Masyarakat Desa Usor Tolang terhadap Pendidikan Karakter Berbasis Islami - Nugraha Andri Afriza; Fadhil Akbar; Siti Ramadhani; Tuti Alawiyah; Nur Azizah Pulungan; Ahmad Faisal; Rahmat Muhaimin; Siti Fatimah Rahmila; Nur Azizah; Mei Efriyana; Dara Mutiara (Lembaga Pengembangan Kinerja Dosen, 2025)
This journal discusses efforts to increase the understanding of the people of Usor Tolang Village regarding Islamic-based character education through the Community Service Program (KKN) of STAIN Madina students. This research uses the Participatory Action Research (PAR) method, which involves the active participation of the community in analyzing and improving ongoing practices. The programs implemented include evening study sessions for elementary school children, training on tajhizul mait (funeral management), seminars on preventing drug abuse, online gambling, and early marriage, as well as teaching activities in elementary schools and MDTA. The aim of this program is to enhance the community's understanding of the importance of character education based on Islamic teachings. Through the approaches of hiwar, qishah, amtsal, uswah, habituation, ibrah, maun'izhoh, targhib, and tarhib, the community is taught not only knowledge but also behavior changes to shape positive character. The results show a significant increase in the understanding and application of Islamic-based character education values among the people of Usor Tolang Village, making a tangible contribution to creating positive social change.